New mixed‐mode second‐generation voltage conveyor based first‐order all‐pass filter. Issue 6 (9th September 2020) - Yuce, Erkan; Safari, Leila; Minaei, Shahram; Ferri, Giuseppe; Stornelli, Vincenzo
Abstract : A new plus‐type second‐generation voltage conveyor (VCII+) based first‐order mixed‐mode (MM) all‐pass (AP) filter is proposed in this study. The proposed MM AP filter employs two VCII+s, three resistors and one grounded capacitor. It has low input and high output impedances for the current‐mode selection while it has low input and low output impedances for the transimpedance‐mode selection. The AP filter gain is unity for the current output while it is adjustable for the voltage output via a grounded resistor. However, a single passive component matching condition is needed for the proposed MM AP filter. Complete non‐ideal analysis by taking into account all the parasitic resistors and non‐ideal gains of the VCII+ is performed. The presented theory is verified through SPICE simulations by using supply voltage of ± 0.9 V and 0.18 μm Taiwan Semiconductor Manufacturing Company complementary metal oxide semiconductor technology parameters.